The Cathedral of Bourges: A Witness to Judeo-Christian Dialogue in Medieval Berry - Jennings, Margaret (Studies in Christian-Jewish Relations, 2011)
Begun in 1195, just one year after Chartres, and essentially finished thirty-seven years later, the high Gothic Cathedral of Saint Stephen at Bourges en Berry rose at an auspicious time for Jewish-Christian relations. Several factors impacted positively on the latter. Among them are Berry's position in central France, far from anti-Jewish centers, the Cathedral's deacon, William of Bourges, a renowned scholar and converted Jew, and the cadre of Christian Hebraists, nourished and developed by Deacon William, who disseminated respect for Jewish tradition. The usually ephemeral "respect" was translated at Bourges into several physical structures at the growing cathedral where, in glass and stone, the dialogue between the communions was imaged. Of the many illustrations of this testimony, three are noteworthy: the cathedral's large clerestory windows are assigned in equal numbers to representatives of the Hebrew and Christian scriptures; its decoration, especially in possibly incendiary scenes like the stoning of Stephen, abjures the hate-filled faces found in other venues; most significantly, its spandrel sculptures, just above eye-level on the Western end, portray various characters and events from Creation through Noah according to the rich perspective of the midrash. Unfortunately, the building campaigns at the cathedral and the respectful interaction between Jews and Christians ceased at almost the same time; nevertheless, St. Stephen's still stands as a witness to its once vibrant presence.